Implementasi Nilai Pendidikan Islam Dalam Pembelajaran Sains Di Perguruan Tinggi - Nurhilaliyah; Dalilul Falihin (CV. SINAR HOWUHOWU, 2026)
This study aims to describe the implementation of Islamic educational values in science learning at higher education institutions. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation techniques. The findings reveal that the implementation of Islamic educational values is carried out through the integration of Qur’anic verses and Hadith into science learning materials, the cultivation of Islamic ethical values such as honesty, discipline, and responsibility, as well as the application of integrative learning strategies based on Islamic values. The implementation has a positive impact on enhancing students’ understanding of scientific concepts, fostering religious character, and increasing social awareness. However, several challenges remain, including the limited availability of integrative teaching materials and the insufficient competence of lecturers in linking scientific knowledge with Islamic values. Therefore, curriculum development and professional training for educators are necessary to optimize the integration of Islamic educational values into science learning at higher education institutions.